Penggunaan Metode Discovery Learning Untuk Meningkatkan Keaktifan Dan Prestasi Belajar Siswa Pada Mata Pelajaran Keterampilan Kelas XI IPA2 Semester 2 Tahun Pelajaran 2021/ 2022 - Sihono Setyo Budi (Universitas Alma Ata, 2022)
This research is aimed to find out if Discovery Learning Model can improve the active and learning achievement at class XI IPA2 in MAN 1 Kulon Progo. The subject of this reasearch is the students of MAN 1 Kulon Progo at class XI IPA2 for 24 students. The datum are obtained by using observation sheet and quantitative and qualitative data analysis. It is shown that there are significant improvements on cycle I, cycle II , and cycle III. The average scores of learning active are 58,20, on cycle I, 62,23 on cycle II and 66,92 on cycle III. The learning achievements also show significant improvement between cycle I, cycle II and cycle III. The average scores of learning achievement are 74,38 on cycle I, 77,75 on cycle II and 79,17 on cycle III. Keywords: Discovery Learning Model, Learning Active, Learning Achievement